1999
DOI: 10.1103/physrevb.59.15729
|View full text |Cite
|
Sign up to set email alerts
|

Self-interstitial–hydrogen complexes in silicon

Abstract: The vibrational properties of interstitial silane (SiH 4) i and silyl (SiH 3) i molecules in crystalline silicon are calculated using a first-principle, cluster based, spin-polarised local-density method. The Si-H stretch modes are found to be red-shifted by ∼ 300 cm −1 from those of the isolated molecule which lie around 2200 cm −1. These results refute recent suggestions that modes observed around 2200 cm −1 , and previously assigned to hydrogenated vacancy defects, are due to these interstitial molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…For defect structures in Si the frequencies determined by Fourier transform infrared spectroscopy 17 48 who calculated that the stretch modes of interstitial silane (SiH 4 ) were lowered by 300 cm Ϫ1 from those of the isolated molecule (ϳ2000 cm Ϫ1 , see Table II͒. In Fig.…”
Section: Vibration Frequenciesmentioning
confidence: 99%
“…For defect structures in Si the frequencies determined by Fourier transform infrared spectroscopy 17 48 who calculated that the stretch modes of interstitial silane (SiH 4 ) were lowered by 300 cm Ϫ1 from those of the isolated molecule (ϳ2000 cm Ϫ1 , see Table II͒. In Fig.…”
Section: Vibration Frequenciesmentioning
confidence: 99%
“…Therefore, Mukashev et al 4 concluded that the 2223 cm −1 LVM was due to VH 4. This attribution is substantiated by ab initio calculations of the frequency 7 In addition to the above-discussed triply degenerate T 2 mode, a center like VH 4 or i-SiH 4 also displays a singly degenerate breathing stretch mode with A 1 symmetry, where the four Si-H bonds of the center vibrate in phase. Such a mode is infrared (IR)-inactive, but Raman-active.…”
Section: Introductionmentioning
confidence: 65%
“…They are transformed into spherical voids by annealing at around 1100 C in a hydrogen atmosphere [136][137][138][139][140]. Experimentally, different techniques have been explored over the years.…”
Section: Layer Transfer Process From Porous Siliconmentioning
confidence: 99%